PENGARUH PENDIDIKAN KESEHATAN TENTANG ABORTUS PROVOCATUS CRIMINALIS TERHADAP PENGETAHUAN REMAJA PUTRI DI SMK COKROAMINOTO KOTA MANADO - Tamunu, Esther N. (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2018)
Abortion acts carried out by teenagers illegally have an impact, both physically and psychologically. Every year in Indonesia there is an increase in cases of abortion around 15% and of these 800,000 of them are carried out by young women who are still students.  This study aimed to determine the effect of health education on criminalis provocatus abortion on the level of knowledge of teenage girl.The research design used was pre-experimental one-group pre-post-test design to compare knowledge before and after being given health education about criminalis provocatus abortion. The study population was all teenage girl in the SMK Cokroaminoto Manado City, amounting to 49 people. The sample technique used is totall sampling, which is as many as 49 people. Analysis by Wilcoxon signed rank test. The test results have a significant influence on health education about criminalis provocatus abortion on the level of knowledge of teenage  girl (? 5 0.05, p-value = 0,000). The conclusion is that health education about criminalis abortion has increased the knowledge of young women. Keywords: Abortus Provocatus Criminalis, Teenage Girl